The Effect of Murabahah, Mudharabah, and Musharakah Financing on Net Profit Growth in Bank Muamalat Indonesia - Erwin Saputra Siregar; Irmayuliana Irmayuliana (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
This study aims to examine the effect of Murabahah, Mudharaba, and Musharaka Financing on Net Profit Growth at Bank Muamalat Indonesia Period 2016-2019. The independent variables used are Murabahah, Mudharaba, and Musharaka financing. The dependent variable used is Net Profit at Bank Muamalat Indonesia. The population and sample in this study are the Monthly Financial Statements of Bank Muamalat Indonesia, January 2016 - December 2019, 12 months x 4 years = 48, so the sample of this research is 48. Samples were selected using the saturated sampling method. The analytical method used in this study is multiple linear regression with time-series data processed using SPSS IBM 20 and Microsoft Excel 2010. The results of this study indicate that the independent variables Murabahah, Mudharaba, and Musharaka financing simultaneously affect the dependent variable Net Profit. Partially Murabahah Financing does not affect Net Profit. Partially, Mudharaba Financing hurts Net Profit, and Partially Musharaka Financing does not affect Net Profit.